Design and Workspace Analysis of Cable-rod Hybrid Drive Parallel Mechanism - Gao Zheng; Zhai Jingshuai; Zhang Jiahan; Li Yajie (Jixie chuandong)
A new type of cable-rod hybrid drive parallel mechanism is proposed，and the overall device model is built in SolidWorks. The inverse kinematics model of the mechanism is derived by using the space vector analysis method. The equilibrium relationship of the parallel platform under static state is analyzed，and the statics equilibrium equation is established. On this basis，the solution method of mechanism controllable workspace is discussed. Under the constraint condition of the given mechanism motion pair，the numerical simulation of the controllable working space of the moving platform posture is carried out to obtain the simulation image. The test platform of the cable-rod hybrid drive parallel mechanism is built. The posture transformation test of the moving platform is completed. The experimental results are compared with the kinematics model and the numerical simulation results of the workspace. The test results show that the relationship between the posture of the moving platform and the length of the cable meets the kinematics inverse solution model. The posture of the end moving platform can be transformed to the maximum posture deflection angle in the workspace simulation image. A theoretical foundation for the practical application and performance optimization of the follow-up institutions is laid by this study.